Penerapan Metode Pembelajaran Take and Give untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PPKn - Amiarti, Cindy Ayu Dwi; Kurniawan, Neo Adhi (Kayon Media, 2023)
: This study aims to describe applying the take-and-give method in Civics at SMPN 1 Gedangan. The type of study was a classroom action study consisting of two cycles. The subjects of the study were 24 students of class VII A. The students' learning outcomes were collected using the study instrument in the form of a written test. The data obtained in the study were analyzed with descriptive quantitative. Based on the results of the study conducted, the application of the Take and Give learning method in Civics subjects at SMPN 1 Gedangan can run well and there is an increase in student learning outcomes in Civics subjects. This can be seen from calculating the average and completeness of classical learning outcomes during pre-action, cycle I, and cycle II. Pre-action obtained an average of 34.2, increased in cycle I with an average of 68.95, and increased by 81.7 in cycle II. At the time of pre-action, there was no learning completeness. Then, in cycle I, we obtained a classical learning completeness of 58.3 percent, and in cycle II, it increased by 83.3 percent.Kajian ini bertujuan untuk mendeskripsikan penerapan metode Take and Give dalam PPKn pada pelajaran PPKn di SMPN 1 Gedangan. Jenis kajian yang dilakukan adalah kajian tindakan kelas yang terdiri dari dua siklus. Subjek kajian adalah 24 orang murid kelas VII A. Hasil belajar murid dikumpulkan menggunakan instrumen kajian berupa tes tertulis. Data yang diperoleh dalam kajian dianalisis dengan deskriptif kuantitatif. Berdasarkan hasil kajian yang dilakukan penerapan metode pembelajaran Take and Give pada mata pelajaran PPKn di SMPN 1 Gedangan dapat berjalan dengan baik serta terdapat kenaikan hasil belajar murid pada mata pelajaran PPKn. Hal ini dapat dilihat dari perhitungan rata-rata dan ketuntasan hasil belajar klasikal saat pra-tindakan, siklus I dan siklus II. Pra-tindakan diperoleh rata-rata 34,2 meningkat pada siklus I dengan rata-rata sebesar 68,95 dan pada siklus II meningkat dengan rata-rata 81,7. Pada saat pra-tindakan belum terdapat ketuntasan belajar kemudian pada siklus I diperoleh ketuntasan hasil belajar klasikal sebesar 58,3 persen dan pada siklus II meningkat sebesar 83,3 persen.